Succession, Identity, and Consumption Scale of Prescriptive Ageism: Italian Validation and Invariance by Gender and Age - Anna Rosa Donizzetti; Cristina Curcio; Michael S. North (Behavioral Sciences)
The aim of the work was to achieve the Italian validation of the Succession, Identity, and Consumption Scale of Prescriptive Ageism (SIC) developed by North and Fiske. SIC is a measure of prescriptive ageism, which incorporates intergenerational tensions over practical and symbolic resources. To evaluate the psychometric properties of the Italian version of the scale, two studies were conducted. Study 1 included 931 Italian participants (mean age: 30.94; range: 18–67 years; 50.5% female) and was conducted to test the scale’s structure and construct validity. Study 2 comprised 1015 Italian participants (mean age: 30.73 years; age range: 18–67; 53.5% female) and investigated the scale’s structure, construct validity, and invariance by gender and age. Confirmatory factorial analyses confirmed the three-factor solution to be invariant across sex and age groups. The scale also demonstrated high internal reliability. SIC scores correlated positively with traditional measures for detecting prejudice and stereotypes towards older people. The results of the present work show that the SIC scale of Prescriptive Ageism is a valid tool for measuring prescriptive beliefs about older adults that are the basis of intergenerational tensions.